2018
DOI: 10.1111/iar.12250
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and geochronological studies of the Muong Hum alkaline granitic pluton from the Phan Si Pan Zone, northwest Vietnam: Implications for petrogenesis and tectonic setting

Abstract: The Phan Si Pan zone in northwest Vietnam is an important tectonic unit for understanding the geological evolution of the southeast Asian Block. Numerous late Permian A‐type granites outcrop in this zone. In this study, new geochemical and geochronological data derived from the Muong Hum alkaline granitic pluton in the Phan Si Pan zone were investigated for its petrogenesis and tectonic setting. Zircon U–Pb analyses of three samples yielded 206Pb/238U ages of (251.1 ±3.5) Ma, (251.2 ±3.8) Ma, and (253.9 ±1.5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
(141 reference statements)
1
4
0
Order By: Relevance
“…Using the internal structure features of zircons and their high Th/U ratios >> 0.1 (Table 4), we concluded that the magmatic rocks of the BG-QS complex were emplaced between 285 and 278 Ma years ago, corresponding to the early Permian period. These ages are similar to those reported by [51] (in Vietnamese with an English Abstract) but show a narrow range and are relatively older than previously published geochronological data (242-266 ± 4.4 Ma by hornblende Ar-Ar, Hung 1999; 251-271 Ma by biotite K-Ar, Khai 1979; and 300 ± 16 Ma by biotite K-Ar, Bao 1979).…”
Section: Emplacement Age Of the Ben Giang-que Son Complexsupporting
confidence: 89%
See 1 more Smart Citation
“…Using the internal structure features of zircons and their high Th/U ratios >> 0.1 (Table 4), we concluded that the magmatic rocks of the BG-QS complex were emplaced between 285 and 278 Ma years ago, corresponding to the early Permian period. These ages are similar to those reported by [51] (in Vietnamese with an English Abstract) but show a narrow range and are relatively older than previously published geochronological data (242-266 ± 4.4 Ma by hornblende Ar-Ar, Hung 1999; 251-271 Ma by biotite K-Ar, Khai 1979; and 300 ± 16 Ma by biotite K-Ar, Bao 1979).…”
Section: Emplacement Age Of the Ben Giang-que Son Complexsupporting
confidence: 89%
“…Histograms of zircon ꜪHf(t) values (a); Hf model age (TDM2) from the BG-QS magmatic rocks (b); and initial ꜪHf values and Hf model ages of zircons (c,d) from this study, Vietnam (modified after[2]). Comparison data are from[2,[5][6][7]12,13,[47][48][49][50][51][52].…”
mentioning
confidence: 99%
“…The previous studies suggested that the Indochina block was formed by welding of continental and microcontinental plates such as South China, Sibumasu and Simao that separated from the Gondwana supercontinent (Lan et al 2000;Hoa et al 2008;Shu et al 2008;Kemp et al 2009;Cawood et al 2011;Liu et al 2012, Hieu et al 2013, 2017, Faure et al 2014 2015; Minh et al 2018), being related to the Emeishan Plume (Figures 8,9 and 13). Within the territory of Vietnam, the collision boundaries are mainly recognized in the Truong Son belt and the Kontum massif.…”
Section: Implications For Regional Geologymentioning
confidence: 96%
“…1000 km from the Gulf of Tonkin to the southeast corner of the Tibetan Plateau. It is generally considered as an Indochina southeastward extrusion of lithospheric-scale strike-slip up to 500 km because of the India-Asia collision (Faure et al 2014;Minh et al 2018). Along the Red River shear zone, there are high-grade metamorphic rocks.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation